Sudan : 2007 Article IV Consultation and Staff-Monitored Program; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Sudan. (IMF Staff Country Reports; Country Report ;, 2007)
This 2007 Article IV Consultation highlights that Sudan's economic growth continued to be strong in 2006. Overall real GDP increased by 12 percent, despite a lower growth in oil production than previously projected. Non-oil GDP increased by roughly 10 percent-buoyed by a continued recovery in agriculture and strong activity in manufacturing, construction, and services. The fiscal position weakened in 2006, reflecting mostly oil revenue shortfalls. The external current account position also deteriorated, reaching a deficit of roughly 13 percent of GDP.